PENGUATAN NILAI-NILAI KEBANGSAAN MELALUI PEMBELAJARAN PKn DI TENGAH ARUS GLOBALISASI - Dewi SA, Utami (Penerbit CV Tentrem Karya Nusa, 2018)
Globalization is an interesting issue to study. This is because indirectly the influence of globalization has resulted in changes in patterns and models of people's lives, from traditional societies to a more modern and open society. The emergence of globalization is marked by progress in various fields of life, both in the field of communication and information. transportation, economy, politics, socio-culture, defense and security, as well as in other fields. The presence of globalization does have a positive impact on the progress of the nation, but on the other hand globalization also has a negative influence on the Indonesian people. The development of attitudes and culture of weternization (westernized) is a form of negative influence of globalization which is a challenge for the Indonesian people. Therefore, to answer the challenges of the negative influence of globalization, one of the efforts that can be done is through strengthening national values for citizens, including in this case the younger generation. Strengthening this national value can be implemented through Citizenship Education.Key Words: Civic education; National Values; Globalization